Outcome of central venous catheter associated upper extremity deep vein thrombosis in cancer patients. Issue 2 (February 2015) - Delluc, Aurélien; Le Gal, Grégoire; Scarvelis, Dimitrios; Carrier, Marc
Abstract: Introduction: Data on efficacy and safety of using low molecular weight heparin in cancer patients with catheter-related upper extremity deep vein thrombosis is scarce and the risk of recurrent venous thromboembolism after discontinuation of anticoagulation is unknown. Material and methods: We conducted a retrospective cohort study including consecutive cancer outpatients assessed for the management of symptomatic central venous catheter-associated proximal upper extremity deep vein thrombosis. Results: Of 99 included patients, 89 were treated with one month of full therapeutic weight-adjusted dose of low molecular weight heparin followed by an intermediate dose. Median duration of anticoagulation was 124 days (range 40 to 1849). No recurrent venous thromboembolism and two major bleeding episodes occurred during the first 3 months of treatment. Eighty patients were followed-up after anticoagulation discontinuation for a median of 632 days (range 6 to 2495). Central venous line was pulled in all patients in remission and in 26 of the 29 patients (89.6%) with active cancer. Five recurrences were observed during follow-up. The cumulative probability of recurrent venous thromboembolism was higher in patients whose cancer was active at the time of anticoagulation discontinuation as compared with those in remission (22.2% (95% CI: 0 to 40.6) vs. 2.3% (95% CI: 0 to 6.7)). Conclusion: The risk of venous thromboembolism recurrence in patients whose central venous catheter has been pulled out and cancer is in remission appears low following anticoagulation discontinuation and after a minimum of 3 months of full/intermediate dose. Highlights: LMWH seems to be a safe and effective to manage catheter associated UEDVT. LMWH can safely be discontinued when cancer is in remission and catheter is removed. Patients with active cancer have a high risk of recurrent VTE.